Duration, frequency, recency, and type of migraine and the risk of ischaemic stroke in women of childbearing age. Issue 6 (1st December 2002) - Donaghy, M; Chang, C L; Poulter, N
Abstract : Background: Migraine is recognised increasingly as a risk factor for ischaemic stroke in women of childbearing age. Migraine with aura poses a higher risk than migraine without aura. Objective: To investigate further the effect of duration, frequency, recency, and type of migraine on the risk of ischaemic stroke. Methods: Additional analyses of a previously reported multicentre case-control study of the relation between stroke and migraine in women aged 20–44 years. Results: Among 86 cases of ischaemic stroke and 214 controls, the adjusted risk of ischaemic stroke was significantly associated with: (1) migraine of more than 12 years duration, odds ratio (OR) 4.61 (1.27–16.8); (2) initial migraine with aura, OR 8.37 (2.33–30.1); (3) particularly if attacks were more frequent than 12 times per year, OR 10.4 (2.18–49.4). In no case did correction for oral contraception usage significantly alter these odds ratios. Increasing risk of ischaemic stroke was related to a change to increased frequency of headaches (trend p ≤ 0.03). Conclusions: These data support earlier reports of a relation between ischaemic stroke and migraine with aura. The risk seems particularly high in those whose initial migraine type involved aura occurring more than 12 times per year.